Deliberation and confidence change - Heinzelmann, Nora; Hartmann, Stephan (Synthese, 2022)
We argue that social deliberation may increase an agent’s confidence and credence under certain circumstances. An agent considers a proposition H and assigns a probability to it. However, she is not fully confident that she herself is reliable in this assignment. She then endorses H during deliberation with another person, expecting him to raise serious objections. To her surprise, however, the other person does not raise any objections to H. How should her attitudes toward H change? It seems plausible that she should (i) increase the credence she assigns to H and, at the same time, (ii) increase the reliability she assigns to herself concerning H (i.e. her confidence). A Bayesian model helps us to investigate under what conditions, if any, this is rational.
Gesehen am 27.01.2025